A meta-analysis of school-based interventions for student refugees, migrants, and immigrants. Issue 4 (2nd October 2022) - Charbonneau, Sarah; deLeyer-Tiarks, Johanna; Caterino, Linda C.; Bray, Melissa
Abstract: How do mental health practitioners and educators support child migrants, child immigrants, child refugees, and their families? This article examines the scope of current interventions for these populations. A meta-analysis of interventions used in schools over the last two decades is discussed to provide an overview of the current evidence base in this area worldwide. Recommendations are made to facilitate the application of these interventions to support child-migrants, child-immigrants, and child-refugees in the schools, and their families.